Design of the School-Enterprise Cooperation Management Information Platform Based on the B/S Architecture - Qiang Zhang (Hindawi Limited, 2021)
The SEC teaching management platform provides a good support for school-enterprise cooperation. This paper conducts research on the SEC management information platform based on the B/S architecture. On the basis of the analysis of the relevant functional needs of the system, the overall functional framework of the system includes the college management platform, enterprise management platform, resource-sharing platform, and user login platform, then the B/S architecture is used to develop the SEC teaching management platform, and the test experiments of the SEC teaching management platform are carried out. The maximum number of concurrent tests shows that the maximum number of concurrencies of the platform is 989. Through the system response time test, the system response time is between 0.2 and 0.45, which meets the system response time requirements. In the CPU use test, the CPU share of the system was between 25% and 31%, meeting the needs of the system. From the above experimental results, the system is relatively high.